Cyaarside (CAs−) and 1, 3‐Diarsaallendiide (AsCAs2−) Ligands Coordinated to Uranium and Generated via Activation of the Arsaethynolate Ligand (OCAs−). Issue 6 (9th January 2019) - Hoerger, Christopher J.; Heinemann, Frank W.; Louyriac, Elisa; Rigo, Massimo; Maron, Laurent; Grützmacher, Hansjörg; Driess, Matthias; Meyer, Karsten
Abstract: Reaction of the trivalent uranium complex [(( Ad, Me ArO)3 N)U(DME)] with one molar equiv [Na(OCAs)(dioxane)3 ], in the presence of 2.2.2‐crypt, yields [Na(2.2.2‐crypt)][(( Ad, Me ArO)3 N)U IV (THF)(μ‐O)(( Ad, Me ArO)3 N)U IV (CAs)] (1 ), the first example of a coordinated η 1 ‐cyaarside ligand (CAs − ). Formation of the terminal CAs − is promoted by the highly reducing, oxophilic U III precursor [(( Ad, Me ArO)3 N)U(DME)] and proceeds through reductive C−O bond cleavage of the bound arsaethynolate anion, OCAs − . If two equiv of OCAs − react with the U III precursor, the binuclear, μ‐oxo‐bridged U2 IV/IV complex [Na(2.2.2‐crypt)]2 [(( Ad, Me ArO)3 N)U IV 2 (μ‐O)(μ‐AsCAs)] (2 ), comprising the hitherto unknown μ:η 1, η 1 ‐coordinated (AsCAs) 2− ligand, is isolated. The mechanistic pathway to 2 involves the decarbonylation of a dimeric intermediate formed in the reaction of 1 with OCAs − . An alternative pathway to complex 2 is by conversion of 1 via addition of one further equiv of OCAs − . Abstract : Rock 'n' Roll cyaarside : Reaction of a strongly reducing oxophilic U III precursor with arsaethynolate (OCAs − ) yields dinuclear uranium complexes with an η 1 ‐bound cyaarside ligand (CAs − ) and a unique diarsaallendiide (AsCAs 2− ) bridging ligand. Both ligands are new to metal coordination chemistry, and the CAs − ligand currently presents the heaviest analogue of the ubiquitous cyanide.